Motives for post-metaphysical thinking - Habermas, Jürgen; Montoya, Jorge (Estudios de Filosofía, 1990)
The state of philosophizing today has become unclear. I do not mean the dispute of the philosophical schools, which was always the medium through which philosophizing moved. I am thinking of the dispute over a premise on which, after Hegel, all parties had initially relied. Today the position on metaphysics has become unclear.